Prevention of personal data privacy leakage in e-government, as the government’s responsibility - Yayang Nuraini Zulfiani (Goodwood Publishing, 2021)
Purpose: Data protection of Personal rights needs to be a priority in upholding human rights and the need for strong institutions to protect them. Personal data protection in Indonesia needs to renew the authority of institutions or by creating new institutions. Research Methodology: the research was carried out using descriptive and normative qualitative research methods with library sources. Results: the results which laws and state institutions overseeing the protection of privacy data in Indonesia need to be improved through the renewal of the legal basis and the renewal of the authority of certain institutions or can also refer to the formation of new institutions related to the security of public personal data to prevent bureaucratic pathologies related to personal data and prevent cyber-crime regarding personal data. Limitations: E-Government and the laws of Personal data privacy Contribution: This study discusses the legal basis for the importance of personal data protection and the importance of reforming central and regional institutions that are authorized to carry out personal data protection for the Indonesian people.